2017
DOI: 10.1128/jvi.02104-16
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Organization of Influenza Virus Proteins in the Budozone Region of the Plasma Membrane

Abstract: Influenza virus assembles and buds at the plasma membrane of virusinfected cells. The viral proteins assemble at the same site on the plasma membrane for budding to occur. This involves a complex web of interactions among viral proteins. Some proteins, like hemagglutinin (HA), NA, and M2, are integral membrane proteins. M1 is peripherally membrane associated, whereas NP associates with viral RNA to form an RNP complex that associates with the cytoplasmic face of the plasma membrane. Furthermore, HA and NP have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 93 publications
(135 reference statements)
6
50
1
Order By: Relevance
“…We first sought to characterize the organization and dynamics of proteins in the viral membrane. By labeling HA and NA, along with the viral nucleoprotein, NP, we are able to measure features of virus organization on intact, infectious particles that corroborate and extend previous observations made using electron microscopy (Calder et al, 2010;Chlanda et al, 2015;Harris et 35 al., 2006;Leser and Lamb, 2017). Images of viruses with labeled nucleoprotein (NP, the most abundant protein in vRNP complexes and a proxy for the virus genome) reveal individual foci of NP that localize to one of the virus's poles, which we use as a fiducial mark for comparing HA and NA localization along the viral envelope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first sought to characterize the organization and dynamics of proteins in the viral membrane. By labeling HA and NA, along with the viral nucleoprotein, NP, we are able to measure features of virus organization on intact, infectious particles that corroborate and extend previous observations made using electron microscopy (Calder et al, 2010;Chlanda et al, 2015;Harris et 35 al., 2006;Leser and Lamb, 2017). Images of viruses with labeled nucleoprotein (NP, the most abundant protein in vRNP complexes and a proxy for the virus genome) reveal individual foci of NP that localize to one of the virus's poles, which we use as a fiducial mark for comparing HA and NA localization along the viral envelope.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether or not virus morphology contributes directly to virus transmission -and if so, how -remains unclear. Similarly, although the two major envelope proteins of IAV, HA and NA, have been observed by electron microscopy to cluster non-uniformly on both the viral and pre- 15 viral envelope (Calder et al, 2010;Harris et al, 2006;Leser and Lamb, 2017), whether and how the spatial organization of HA and NA affects virus transmission remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work we have investigated for the first time the interaction between IAV M1 and free-standing model membranes containing different amounts of PS. The protein concentration (much larger than the reported K d values (8,33)) was chosen so to take into account that, in vivo, viral proteins might be recruited in small PM domains (40) and, therefore, reach a high local concentration (41). Previous investigations on solid-supported bilayers have demonstrated that M1 binds to lipid membranes containing negatively-charged lipids and that M1-lipid binding is accompanied by extensive protein multimerization (7).…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence contradicts the idea M2 is associating with nano-domains (or socalled "rafts") (31) and that the CRAC sequence plays a role herein (32). Nonetheless, the presence of a molecular specificity pocket on M2 toward cholesterol might provide general affinity toward the budozone area (33) or in the later stage of budding (34). While structural modulators of M2 (such as cholesterol) might affect the CG model if for instance cholesterolbinding activity can change the affinity of M2 towards the Lo budozone, it appears that M2 recruitment to the budozone is due to interactions with the matrix protein and not due to the cholesterol-binding activities.…”
Section: Cg Model and Correspondence With In Vivo And In Vitro Systemsmentioning
confidence: 96%